Morphofunctional features of endometrium in women with combination of male and female factors - O. M. Nosenko; A. I. Seylova (Kazimierz Wielki University, 2019)
Treatment couples with a combination of male and female factor infertility is the most difficult and often requires precisely ART. However, ICSI efficacy currently does not exceed 35-40 %, about a third of all pregnancies are terminated early. The purpose of the study was to determine the morphofunctional features of endometrium in women from married couples with a combination of female and male factors of infertility. Material and methods. There were 100 married couples with prospective follow-up with a combination of male and female infertility factors of group A who had applied for assisted reproductive technologies (ART). All men in group A suffered from pathozoospermia. Control group C consisted of 34 couples with secondary infertility of tube genesis, who consisted of conditionally somatically healthy women with a history of childbirth, without fallopian tubes, and their men with normozoospermia. Group A was stratified each into 3 subgroups. The A1 subgroup (n = 32) included married couples who had chronic anovulation; in subgroup A2 (n = 37) - married couples who had tubal infertility; in subgroup A3 (n = 31) - married couples in which women had a combination of tubal and anovulatory factors of infertility. Material for morphological examination were endometrial pipel-biopsy specimens on day 21-22th of the menstrual cycle on the day of the expected implantation window. It were determined expression of HOXA10, Leukemia inhibitory factor (LIF), glycoprotein 130 (gp130), interleukin-6 (IL-6) in endometrium. Results: morphofunctional status of women's endometrium with a combination of female and male infertility factors was characterized by an increase in estrogen-α receptor IRS in the glands and endometrial stroma, respectively, 1.86 (p